Minimal Total Area Convex Set Partitioning Problem - Stefan Pesko (Communications - Scientific letters of the University of Zilina, 2009)
The linear binary model for finding set partitioning of the points in the plane is studied.We present heuristic which generates partitioning of points to clusters for a given number of seeds with searched seeds of clusters in a plane. For this cluster the convex hulls are constructed via Graham’s scan algorithm. This approach is demonstrated on the real instance of Florida area with 235 points for 10 and 13 clusters.